P Penilaian Kinerja Supplier Berkah Rahayu Jaya Tapioka Menggunakan Metode Performance Prism dan AHP - arrohman, hernanda rifqi (nter of Execellence (COE) ICT Infrastructure, Smart Manufacture and Digital Supply Chain, 2025)
Berkah Rahayu Jaya Tapioca is a company that produces tapioca flour. This company has problems related to suppliers who deliver raw materials not according to production time, the quality of raw materials that are less than expected, and the price of raw materials that are not competitive, causing the quality and quantity of products produced to be not optimal. Therefore, companies need to use Key Performance Indicators (KPIs) as benchmarks to identify suppliers who meet company standards and to evaluate suppliers, enabling them to identify the best ones. The purpose of this research is to find out what KPIs can be used to assess the performance of raw material suppliers and determine the best raw material suppliers. The methods used in this research are performance prism and AHP. The results of this study are KPIs used to assess raw material suppliers; there are 3 criteria, including increasing profits (5 subcriterion), maintaining cooperation (2 subcriterion), and increasing trust (2 subcriterion). Furthermore, the KPI weighting results obtained the weight of the Bpk. Arifudin (Cipicung) supplier at 0.383, the Bpk. Subagyo (Pekuncen) supplier at 0.173, the Bpk. Tarso (Kr.tawang) supplier at 0.155, the Bpk. Hasan (Ciputih) supplier at 0.117, the Bpk. Hudi (Binangun) supplier at 0.095, and finally the Bpk. Rohman (Grnggng) supplier at 0.074. Keywords: Performance Prism, Key Performance Indicator, AHP